Assessment of reflux symptom severity: methodological options and their attributes. (13th April 2004) - Bytzer, P
Abstract : Despite major advances in our understanding of reflux disease, the management of this disorder still presents many challenges. Reduction of heartburn is the most readily apparent objective for the patient with reflux disease. Thus the ability to measure heartburn accurately is of fundamental importance to clinical research in reflux disease. Here, the available data on the assessment of reflux symptoms—predominantly heartburn—in clinical trials of symptomatic reflux disease are examined.